A novel precision evaluation and analysis method for the direct driven high-speed feed system. (15th April 2019) - Yang, Xiaojun; Liu, Hui; Yang, Qingyu; Zhao, Wanhua
Highlights: A novel precision evaluation method and indexes are proposed for direct driven feed system. Dynamic precision is analytical represented considering multi-source inputs and disturbances. The main influencing factors of each index are discussed based on the sensitivity analysis. Abstract: The direct driven feed system incorporates the merits of simple structure, high velocity and high acceleration, which has a bright future in the high-speed machine tools. However, because of the absence of the intermediate transmission components, there are different kinds of the disturbances which directly act on the mechanical system, leading to multiform motion errors. The complex motion errors in different motion processes will affect the final dynamic performance of the feed system with different forms and degrees, and finally affect the machining precision of the workpiece. It is of great significance to find a comprehensive and systematic precision evaluation method for the analysis and improvement of the dynamic precision of the feed system. In this paper, based on the motion characteristics and error sources, a novel precision evaluation and analysis method and indexes are proposed for the direct driven feed system. The electromechanical integrated model is established and then the dynamic precision in different motion processes with multi-source inputs are analytical presented. What is more, the experimental verification is carried out with different velocities. The results demonstrate that the proposed method can systematically evaluate the dynamic performance of direct drive high-speed feed system. Finally, the sensitive parameters of the precision evaluation indexes are discussed using the sensitivity analysis method (SAM), and the corresponding improvement measures are put forward.